Scaling-up and strengthening of climate services promotes knowledge democratization and practice adoption across Latin America - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
CCAFS scientist and regional and national partners have scaled out Local Technical Agroclimatic Committees (LTAC), to assess, co-produce, translate and transfer climate information to enable agricultural decision making. A major transformation is found in Latin America regarding knowledge democratization and practice adoption. Through LTACs, farmers receive information to adapt their productive practices by making decisions based on the information they receive about climate variability, reducing losses and increasing profitability.